Sports and Combat SAMBO Exposure and Differences in Stage-Activity - Stanislav Dadelo; Algis Mečkovskis; Edmundas Štarevičius (Lithuanian Sports University, 2018)
Research  background  and  hypothesis.  The  sport  result  is  mostly  accounted  for  by  the  technical  and  tactic preparation of SAMBO fighters. The establishment of the Sports and Combat SAMBO wrestling contest actions will allow identifying the essential differences between the ways of wrestling. Research aim was to examine the distribution of actions used by Lithuanian Sport and Combat SAMBO fighters exhibiting different sport skill levels at contests differing in terms of their level. Research methods. In 2012 we watched 46 Lithuanian higher school Sport SAMBO contest bouts and analysed 50 Lithuanian Sport SAMBO Championship bouts and 43 Combat SAMBO bouts. Research results. Actions performed at Sport SAMBO were relatively divided into: very important - throws by legs and throws by trunk; important - throws by arms and retention; of minor importance - painful arm locks and painful leg locks. Combat SAMBO wrestling actions were divided into: very important - throws by arms, retention and throws by trunk; important - throws by legs, painful arm locks; of minor importance - painful leg locks. Discussion and conclusions. In stage-activity, the arsenal of greater mastery SAMBO wrestling moves and combinations is larger, therefore the process of drafting motion management training should be the main objective. Throws  performed  on  stage  by  Sports  and  Combat  SAMBO  wrestling  wrestlers  have  major  differences.  Sport  SAMBO is based on a large variety off throws, in sport SAMBO the throw is attempted by feet or waist, and combat  SAMBO wrestling is based on hand throws, throws around the waist, maintenance, leg locks and arm bars. Keywords: competition stenography, range of actions, effectiveness of actions.